Mapping Net Primary Productivity of Peninsular Malaysia Forest Using Satellite Data - Ibrahim, Ab. Latif (National Institute for Environmental Studies, Japan, 2005)
The main objective of this project is to estimate and map the Net Primary Productivity (NPP) of Peninsular Malaysia forest using NOAA AVHRR satellite data. The production of this NPP map is very important and serves as background information for the overall project, the mapping of ecosystem services and goods for the tropical rain forest that is still on-going. For this purpose, series of NOAA satellite data for the year 2004 have been pre-processed, first to precisely co-register each image through geometric correction and secondly the radiometric corrections were performed to eliminate the radiometric distortions mainly caused by incidence angle different of sun light. As most of the images obtained were covered with cloud, cloud free image was then generated by combining and mosaicking images of difference dates. Apart from satellite image, meteorological parameters such as surface solar irradiance, surface temperature and rainfall were obtained from Malaysian Meteorological services as an input into the model Results of the analysis indicate that the annual values NPP are within the range of 50 to 6,000 gC/m2/year, while the values of Normalized Differential Vegetation Index (NDVI) are within the range of 0.04 to 0.7.